2019
DOI: 10.3390/cancers11121871
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy-Dependent Reactivation of Epstein-Barr Virus Lytic Cycle and Combinatorial Effects of Autophagy-Dependent and Independent Lytic Inducers in Nasopharyngeal Carcinoma

Abstract: Autophagy, a conserved cellular mechanism, is manipulated by a number of viruses for different purposes. We previously demonstrated that an iron-chelator-like small compound, C7, reactivates Epstein-Barr virus (EBV) lytic cycle by activating the ERK1/2-autophagy axis in epithelial cancers. Here, we aim to identify the specific stage of autophagy required for EBV lytic reactivation, determine the autophagy dependency of EBV lytic inducers including histone deacetylase inhibitor (HDACi) and C7/iron chelators, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 39 publications
(85 reference statements)
0
15
0
Order By: Relevance
“…219 LINC00460 is highly associated with the EMT in NPC cells via binding miR-30a-3p to regulate the expression of Rasrelated protein 1A (Rap1A). 220 What's more, patients whose infiltrating lymphocytes are characterized by high expression of lncRNA AFAP1-AS1 incline to distant metastasis and poor prognosis, especially with positive PD1. 221 N,N′-dinitrosopiperazine (DNP) can promote proliferation, invasion, and metastasis of NPC by enhancing the expression of miR-149 which suppresses the level of PKP3.…”
Section: Non-coding Rna Related To Targeted Therapy Of Npcmentioning
confidence: 99%
“…219 LINC00460 is highly associated with the EMT in NPC cells via binding miR-30a-3p to regulate the expression of Rasrelated protein 1A (Rap1A). 220 What's more, patients whose infiltrating lymphocytes are characterized by high expression of lncRNA AFAP1-AS1 incline to distant metastasis and poor prognosis, especially with positive PD1. 221 N,N′-dinitrosopiperazine (DNP) can promote proliferation, invasion, and metastasis of NPC by enhancing the expression of miR-149 which suppresses the level of PKP3.…”
Section: Non-coding Rna Related To Targeted Therapy Of Npcmentioning
confidence: 99%
“…Table 1 summarizes the efficiencies of EBV lytic induction by the different compounds from multiple studies. In general, HDAC inhibitors such as NaB could reactivate 2–60% of EBV-positive B cells into lytic cycle, while SAHA could reactivate 30–65% of EBV-associated epithelial cells (AGS-BX1, HA, and HK1-EBV) into lytic cycle [ 45 , 46 , 47 ]. VPA could induce around 10% of AGS-EBV cells, while the percentage was low in LCL and C666-1 cells [ 48 ].…”
Section: Weaknesses and Concerns Related To The Lytic Inducing Commentioning
confidence: 99%
“…Novel compounds identified by our group such as C7, E11, C8, E7, and A10 could induce 30–60% of AGS-BX1 cells into lytic cycle [ 42 ]. Follow-up studies on C7, the best-performing compound identified, showed its ability to induce 6–12% of HA, C666-1, and NPC43 cells into lytic cycle [ 36 , 46 ]. Another new class of compounds, curcuminoids, were shown to induce 20–50% of AGS-BX1, C666-1, and HONE1-EBV cells into lytic cycle [ 41 ].…”
Section: Weaknesses and Concerns Related To The Lytic Inducing Commentioning
confidence: 99%
See 2 more Smart Citations